Testing the Dimensionality of Policy Shocks - Li, Jia; Todorov, Viktor; Zhang, Qiushi (The Review of Economics and Statistics, 2024)
Abstract This paper provides a nonparametric test for deciding the dimensionality of a policy shock as manifest in the abnormal change in asset returns’ stochastic covariance matrix, following the release of a macroeconomic announcement. We use high-frequency data in local windows before and after the event to estimate the covariance jump matrix and then test its rank. We find a one-factor structure in the covariance jump matrix of the yield curve resulting from the Federal Reserve’s monetary policy shocks before the 2007–2009 financial crisis. The dimensionality of policy shocks increased afterwards because of the use of unconventional monetary policy tools.